Modeling Dynamically Reconfigurable Systems for Simulation-Based Functional Verification - Lingkan Gong; Diessel, O (2011 IEEE 19th Annual International Symposium on Field-Programmable Custom Computing Machines, 2011)
Dynamically Reconfigurable Systems (DRS), which allow logic to be partially reconfigured during run-time, are promising candidates for embedded and high-performance systems. However, their architectural flexibility introduces a new dimension to the functional verification problem. Dynamic reconfiguration requires the designer to consider new issues such as synchronizing, isolating and initializing reconfigurable modules. Furthermore, by exposing the FPGA architecture to the application specification, it has made functional verification dependent on the physical implementation. This paper studies simulation as the most fundamental approach to the functional verification of DRS. The main contribution of this paper is in proposing a verification-driven top-down modeling methodology that guides designers in refining their reconfigurable system design from the behavioral level to the register transfer level. We assess the feasibility of our methodology via a case study involving the design of a generic partial reconfiguration platform.